Toward a Contextualized View of Voice Quality, Its Dimensions, and Its Dynamics Across Newcomer Socialization - Farh, Crystal I. C.; Li, Junchao (Jason); Lee, Thomas W. (Academy of Management Review, 2024)
As research on employee voice proliferates, there is an emerging interest in understanding the kinds of voice that have greater potential to enhance performance – i.e., the productivity and quality of unit and organizational outputs. Yet existing work in this area has focused primarily on characteristics of voice that appear valued by recipients, falling short in specifying the dimensions that contribute to voice’s performance-enhancing potential or the conditions that facilitate its development in organizations. Envisioning “voice quality” as a cross-level and context-specific phenomenon, we advance a contextualized theory that first draws on an organizational ambidexterity perspective to detail how voice quality is multiplicatively composed of three dimensions – desirability, feasibility, and, in exploration-focused contexts, degree of change. Further recognizing that the development of voice quality depends on context-specific knowledge, experiences, and cognitions, we accentuate how time – in conjunction with other individual and contextual factors – produces ebbs and flows in voice quality in the specific case of newcomer socialization. Altogether, our framework aims to build consensus around a contextualized understanding of the dimensions of voice quality, highlight its dynamic nature, and advance a temporally precise theory around its unique nomological network in organizations.